A Conceptual Mathematical Examination of the Aerosols Loading over Abuja-Nigeria - Emetere, Moses Eterigho; Akinyemi, Marvel; Oladimeji, Temitope (Communications in Mathematics and Applications, 2016)
One of the urban cities in Nigeria known for elevated levels of atmospheric aerosol pollution is Abuja, been the fastest growing city in Nigeria. Due to the health problems associated with this fact, a study of aerosol loading must be prioritized so as to identify the preventive measures required. This study aims at estimating the aerosol loading and retention over Abuja. Statistical AOD analysis for thirteen years was obtained from the Multi-angle imaging spectro radiometer (MISR). Statistical tools, as well as analytically derived model for aerosols loading were used to obtain the aerosols retention and loading over the area. Observations shows that, the highest AOD analysis was found in 2005, the highest skew and kurtosis can be found in 2010 and the highest Kolmogorov-Smirnov stat can be found in 2004. This results shows that the lower atmosphere of Abuja may not be dynamic as cities in the southern Nigeria and proposes an inclusion of the attenuation due to moving aerosols layer into the ITU model which is significant via the atmospheric constants over Abuja. The aerosols retention peak in Abuja occurs every ten years.